GIS-Based 'Banua Siaga' Platform for Enhancing Disaster Preparedness Through Health Post Mapping in Palu - Budiman Budiman; Ahmad Yani; Fatmawati Fatmawati (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Household safety and disaster evacuation are crucial global issues, especially in Southeast Asia, where Indonesia is highly vulnerable to natural disasters. Palu City, Central Sulawesi, frequently experiences disasters such as earthquakes, tsunamis, and landslides, necessitating effective disaster management strategies. The increasing escalation and intensity of disasters demand improved preparedness and response mechanisms. This study aims to develop an interactive platform utilizing Geographic Information System (GIS) technology to map health service posts and evacuation points in Palu City, ensuring real-time access to crucial disaster response information. Methods: This study employs a quantitative descriptive approach with a developmental research design to create an interactive platform for mapping health service posts. The research integrates GIS technology with real-time data collection and community participation mechanisms to enhance disaster preparedness. The research process includes data source verification, user needs analysis through surveys and interviews, platform design and development, and quality control through expert reviews and usability testing. Ethical considerations were followed to ensure participant confidentiality and data security. Results: The developed platform, Banua Siaga, utilizes GIS software to map health service locations and integrates real-time reporting features via Google Forms. Key features include interactive maps, location-based services, and real-time feedback mechanisms. The platform enables users to identify the nearest health post, access available services, and report emergency needs. The GIS-based mapping of 46 health service posts across Palu City ensures strategic placement for optimal disaster response. Initial usability tests indicate improved accessibility, faster response times, and enhanced community engagement in disaster management. Conclusion: The integration of GIS technology in disaster preparedness significantly enhances emergency response efficiency by improving accessibility to health service posts and evacuation routes. Community participation and real-time data integration further strengthen the platform’s effectiveness. Beyond its implementation in Palu City, this approach has the potential to be adapted in other disaster-prone regions, both in Indonesia and globally, to improve disaster preparedness and response. However, challenges such as resource availability, infrastructure limitations, and digital literacy must be addressed for broader implementation. Future research should focus on expanding the platform’s scalability, incorporating AI-driven predictive analytics, and conducting real-world validation through disaster simulations.